Classification as Collective Representation: A Conceptual Review of Durkheim and Mauss's Primitive Classification - Hasan, Fayumi; Aziman, Luthfil; Truna, Doddy S.; Rosyad, Rifki (PT. Hafasy Dwi Nawasena, 2026)
This article examines Émile Durkheim and Marcel Mauss's Primitive Classification as a foundational text in the sociology of knowledge that argues classificatory thinking is not merely an individual cognitive given, but a socially formed institution. Using library research and critical-conceptual analysis, the paper reconstructs the book's central thesis that social divisions (moieties, clans, and totemic groupings) provide the prototype and scheme by which natural phenomena are organized into hierarchical systems of categories. The analysis highlights their comparative cases, including Australian totemic systems, Zuñi and Sioux classifications, and Chinese correlative cosmology, to show how cosmological order and social order are made mutually intelligible through classificatory logics. The article then discusses Rodney Needham's editorial introduction, which questions the explanatory